Pengaruh Metode Game Based Learning Terhadap Kemampuan Motorik Kasar Dan Kemampuan Sosial Emosional Anak TK (The Effect of Game Based Learning Methods on Gross Motor Abilities and Social Emotional Abilities of Kindergarten Children) - Pujayanti, Falsafah Hari; Sumiharsono, Rudy; Triwahyuni , Eges (LP. Ma'arif Janggan Magetan, 2023)
The purpose of this study was to find out whether using the game based learning method could improve gross motor skills and social emotional abilities of group B children at Kindergarten Nurul Fatah. Variable X, (game based learning method) 3 indicators. 1) increase learning effectiveness, 2) higher interest in learning, 3) increase learning motivation. Y1 (gross motor) 4 indicators, 1) walking, 2) running, 3) jumping, 4) throwing. Y2 (social emotional) 3 indicators, 1) managing emotions, 2) EXPRESS EMOTIONS, This research design uses causal quantitative. The method of determining the area by purposive sampling area. The population research population research technique consisted of 31 children in group A. Data collection techniques: 1). observation, 2). interview, 3). document. The results of the interviews are then processed into several instrument tests of validity and reliability tests, then the classic assumption test includes the normality test, homogeneity test, autocorrelation test, and heteroscedasticity test, and finally is the hypothesis test which includes the t test and F test. The results are the test results t X to Y1 3.355> 2.048, X to Y2 3.052> 2.048 FX test results to Y1 and Y2 sig <0.05 (0.008 <0.05). So it can be concluded that the game based learning method affects gross motor skills and social emotional abilities.